Quickly understanding on progressive muscle relaxation with video-based learning in secondary school students - Sulaiman, Wan Mohamad Hafiz; Jumintono, Jumintono; Wahyuniati, Christina Fajar Sri; Wiwik Suryandartiwi, Wiwik Suryandartiwi; Jaka Sunardi, Jaka Sunardi; Umar, Fadilah; Manoppo, Febri Kurnia; Yudanto, Yudanto; Hos, Jamaluddin (HRPUB, 2020)
Progressive muscle relaxation can improve students' learning performance in the classroom because it provides a good focus during classroom learning sessions in developing technical communication for educational institutions. This study aims to determine the effectiveness of video-based learning on the understanding of secondary school students related to Progressive Muscle Relaxation. The research was a quantitative descriptive method. Based on research that has been done, researchers found differences in students' understanding between before and after watching videos related to progressive muscle relaxation. In this study, respondents need to answer questions raised by researchers before viewing the video and after watching the video. The respondents in this study were only six students. The percentage of respondents who answered the question correctly after seeing the video provided by the researcher rose quite significantly. Respondents are interested in the video provided, and respondents can understand the video content they want to convey. The use of video in teaching and learning is beneficial for students to increase their interest and demand Progressive Muscle Relaxation knowledge. Video-based learning can be implemented in teaching and learning in various fields of education. Visual lessons are more quickly remembered and understood by students. Learning to use videos can increase student's interest in learning new things.